Relationship Between Complications and Readmissions in Type 2 Diabetes Mellitus Patients in Aceh, Indonesia (International Journal of Nursing Education, 2024)
Introduction: Complications in diabetes mellitus patients are among the causes of hospital readmissions. Readmissions negatively impact patients’ quality of life and increase health and care costs. This study aims to explore the relationship between complications and readmissions in type 2 diabetes mellitus patients.Methods: A correlational study was utilized with a cross-sectional design. A total of 184 readmission patients with type 2 diabetes mellitus were selected as the sample using the accidental sampling technique. Data were collected through a questionnaire consisting of the Diabetes Early Readmission Risk Indicators (DERRI™) and the Readmission Questionnaire providing 4 answer choices, i.e. ≤ 30 days; > 30–60 days; > 60–90 days; and > 90 days. The Chi-square test was employed for data analysis. Results: Of all respondents, the majority are in late adulthood (50-61 years), totaling 70 individuals (38.0%) with a mean age of 57.3 years; 111 individuals (60.3%) are male; 99 (53.8%) have completed elementary education; 102 (55.4%) work as farmers/laborers/fishermen; and 67 (36.4%) use Humalog as their insulin. Moreover, 69 respondents (37.5%) have experienced the third readmission, which is the highest number of readmissions. The bivariate analysis reveal that there is a significant relationship between complications of type 2 diabetes mellitus and patient readmission (p=0.000).Conclusion: The findings demonstrate complications as a factor associated with readmissions of type 2 diabetes mellitus patients. The complications leading to the readmissions include hypoglycemia, hypertension, heart problems, kidney problems, diabetic ulcers, and strokes. Also, age contributes as a factor increasing the readmission risk of patients with type 2 diabetes mellitus. The results emphasize the need to re-evaluate health service strategies and nursing interventions by providing effective discharge planning to prevent complications or reduce readmissions in type 2 diabetes mellitus patients.